STUDI MENGENAI DAMPAK PARIWISATA DI DESA WISATA TEBING TINGGI OKURA KEPADA EKONOMI MASYARAKAT LOKAL - Ningsih, Nursukma Widia; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The existence of a Tourism Village will definitely have an impact on the local community. Therefore, this study aims to determine the impact of the Okura High Cliff Tourism Village on the economy of the local community This research was conducted in Tebing Tinggi Okura Village, Rumbai Pesisir District, Pekanbaru City, Riau. The research method that will be used in this study is Qualitative with the type of Grounded Research. Data collection was carried out by observation, documentation and interview methods by interviewing several residents living in Tebing Tinggi Okura Tourism Village. Through interviews conducted with 8 informants, 4 impacts of the Okura High Cliff Tourism Village were obtained, namely: 1) The Impact of Novelty; 3) the emergence of jobs; 3) the Impact on visits; and 4) the Impact on the Economy. Keywords: Economic Impact, Tourism Village, Local Community